1997
DOI: 10.1016/s0014-5793(97)00261-5
|View full text |Cite
|
Sign up to set email alerts
|

Movement of the 3′‐end of tRNA through the peptidyl transferase centre and its inhibition by antibiotics

Abstract: Determining how antibiotics inhibit ribosomal activity requires a detailed understanding of the interactions and relative movement of tRNA, mRNA and the ribosome. Recent models for the formation of hybrid tRNA binding sites during the elongation cycle have provided a basis for re-evaluating earlier experimental data and, especially, those relevant to substrate movements through the peptidyl transferase centre. With the exception of deacylated tRNA, which binds at the E-site, ribosomal interactions of the 3'-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 144 publications
2
25
0
1
Order By: Relevance
“…Although the contribution of ribosomal components to the formation of peptide bonds is still not understood, it is known that the peptidyl transferase loop region of 23S-like rRNA plays an important role Khaitovich et al+, 1999)+ The results of diverse experimental approaches are consistent with this rRNA region contributing to the binding sites of the 39 termini of both donor and acceptor tRNA substrates and of many antibiotics that are known to inhibit peptide bond formation (reviewed in Kirillov et al+, 1997)+ The approaches include rRNA footprinting and damage-selection analyses of tRNA substrates and antibiotics bound to ribosomes (Moazed & Noller, 1989;Rodriguez-Fonseca et al+, 1995;Bocchetta et al+, 1998) and the characterization, within this rRNA region, of several single-site mutations that confer antibiotic resistance on mutant strains that lead to changes in tRNA substrate binding and/or a lowering of peptidyl transferase activity on isolated mutant ribosomes (e+g+, Porse et al+, 1996; Green et al+, 1997)+ An azido group can be introduced into the 2 position of the 39-terminal adenosine of tRNA such that when the modified tRNA is bound in the P/P9 site, which is identical to the earlier defined P site (Kirillov et al+, 1997), and irradiated with ultraviolet (UV) light at 365 nm, cross-links are generated with 23S rRNA and ribosomal proteins in the P9 site of the 50S subunit (Wower et al+, 1988(Wower et al+, , 1989(Wower et al+, , 1995)+ The rRNA cross-links have been localized within three fragments, F1 (nt 2570-2590), F2 (nt 2500-2520), and F4 (nt 2060-2080), all of which extend into the peptidyl transferase loop region of 23S RNA (Wower et al+, 1995)+ The main crosslinked proteins are L27 (strong) and L33 (weak) (Wower et al+, 1989), both of which assemble on domain V of 23S RNA that contains the peptidyl transferase loop Østergaard et al+, 1998)+ The former protein was also shown earlier to react preferentially with an affinity-labeled peptide moiety linked to a P/P9-site-bound tRNA (Eilat et al+, 1974)+ In this study, we first identified the cross-linked sites at a nucleotide level on the 23S rRNA of azidoderivatized deacylated (2N 3 A76)tRNA and N-Ac-Phe-(2N 3 A76)tRNA bound at the P/P9 site in the presence of poly(U)+ Then we chose several antibiotics that either inhibit peptide bond formation or perturb the nascent peptide on Escherichia coli ribosomes (Table 1) and examined their effects on the cross-linking yields of the azido-derivatized tRNAs to rRNA and ribosomal proteins+ Each antibiotic affected cross-linking yields almost exclusively at the rRNA sites+…”
Section: Introductionmentioning
confidence: 99%
“…Although the contribution of ribosomal components to the formation of peptide bonds is still not understood, it is known that the peptidyl transferase loop region of 23S-like rRNA plays an important role Khaitovich et al+, 1999)+ The results of diverse experimental approaches are consistent with this rRNA region contributing to the binding sites of the 39 termini of both donor and acceptor tRNA substrates and of many antibiotics that are known to inhibit peptide bond formation (reviewed in Kirillov et al+, 1997)+ The approaches include rRNA footprinting and damage-selection analyses of tRNA substrates and antibiotics bound to ribosomes (Moazed & Noller, 1989;Rodriguez-Fonseca et al+, 1995;Bocchetta et al+, 1998) and the characterization, within this rRNA region, of several single-site mutations that confer antibiotic resistance on mutant strains that lead to changes in tRNA substrate binding and/or a lowering of peptidyl transferase activity on isolated mutant ribosomes (e+g+, Porse et al+, 1996; Green et al+, 1997)+ An azido group can be introduced into the 2 position of the 39-terminal adenosine of tRNA such that when the modified tRNA is bound in the P/P9 site, which is identical to the earlier defined P site (Kirillov et al+, 1997), and irradiated with ultraviolet (UV) light at 365 nm, cross-links are generated with 23S rRNA and ribosomal proteins in the P9 site of the 50S subunit (Wower et al+, 1988(Wower et al+, , 1989(Wower et al+, , 1995)+ The rRNA cross-links have been localized within three fragments, F1 (nt 2570-2590), F2 (nt 2500-2520), and F4 (nt 2060-2080), all of which extend into the peptidyl transferase loop region of 23S RNA (Wower et al+, 1995)+ The main crosslinked proteins are L27 (strong) and L33 (weak) (Wower et al+, 1989), both of which assemble on domain V of 23S RNA that contains the peptidyl transferase loop Østergaard et al+, 1998)+ The former protein was also shown earlier to react preferentially with an affinity-labeled peptide moiety linked to a P/P9-site-bound tRNA (Eilat et al+, 1974)+ In this study, we first identified the cross-linked sites at a nucleotide level on the 23S rRNA of azidoderivatized deacylated (2N 3 A76)tRNA and N-Ac-Phe-(2N 3 A76)tRNA bound at the P/P9 site in the presence of poly(U)+ Then we chose several antibiotics that either inhibit peptide bond formation or perturb the nascent peptide on Escherichia coli ribosomes (Table 1) and examined their effects on the cross-linking yields of the azido-derivatized tRNAs to rRNA and ribosomal proteins+ Each antibiotic affected cross-linking yields almost exclusively at the rRNA sites+…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are important tools for the treatment of many serious human and animal infections+ However, the increasing use and misuse of these drugs in both the health care and agricultural sectors have led to increasing problems with drug-resistant bacteria, with severe consequences for human health+ One group of such therapeutically important antibiotics are the streptogramins, which contain A and B components and target the peptidyl transferase center of the large ribosomal subunit, where they inhibit peptide elongation+ Resistance to both streptogramin components is widespread in diverse bacterial communities+ Streptogramins inhibit peptide elongation by a mechanism that is only partially understood+ Moreover, the two components act synergistically such that although the individual A and B components are bacteriostactic, together they can be bacteriocidal (Gale et al+, 1981;Di Giambattista et al+, 1989)+ The observation that neither streptogramin component affects protein synthesis on polysomes suggests that they act during the initial rounds of protein synthesis in vivo (Contreras & Vázquez, 1977)+ In contrast to the A component, streptogramin B has no direct effect on peptide bond formation with puromycin, in vitro, a property which it shares with the smaller macrolides+ Streptogramin B and these macrolides also share a similar resistance mechanism associated with either N-6 methylation (MLS B phenotype), or mutation, at A2058 within the peptidyl transferase loop of 23S rRNA that is important for peptide bond formation (Cundliffe, 1990;Garrett & RodriguezFonseca, 1995)+ The binding sites of both streptogramin components have been assigned indirectly to nucleotides within the peptidyl transferase loop of 23S rRNA on the basis of chemical footprinting and mutational analyses (Vanuffel et al+, 1992;Rodriguez-Fonseca et al+, 1995;Porse & Garrett, 1999) and, for the B component, to the vicinity of ribosomal proteins L18 and L22 by affinity labeling (Di Giambattista et al+, 1990)+ However, although several lines of evidence suggest that these and other peptidyl transferase drugs interact with rRNA, no direct binding to isolated 23S rRNA has been detected for any of them (reviewed by Kirillov et al+, 1997)+ In the present work, we provide evidence for both a direct interaction of the streptogramin B drug, pristinamycin IA (PIA; Fig+ 1), with highly conserved nucleotides of the peptidyl transferase loop of 23S rRNA and for two PIA-dependent modifications in the same functional rRNA region+ Moreover, we demonstrate that the presence of pristinamycin IIA (PIIA, a streptogramin A), chloramphenicol, carbomycin, tylosin, spiramycin and P-site-bound tRNA alter the PIA-induced effects+ Finally, evidence is provided for the binding of PIA to protein-free mature rRNA, and to small rRNA fragments excised from the peptidyl transferase loop region, which is dependent on at least one posttranscriptional modification+…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that resistance to antibiotics often involves a single mutation [4,5] or methylation of a specific nucleotide in a highly conserved structural motif of rRNA [6], confirming the highly specific nature of RNAantibiotic interactions. Recently, the crystal structures of the large 50S subunit [7] and 30S small subunit [8] of ribosomal RNA and their complexes with a number of antibiotics [9,10] have been solved.…”
Section: Introductionmentioning
confidence: 99%
“…1a) [4,5]. However, based on more recent experiments, it has been revealed that antibiotic inhibition of peptide transfer can also take place by other mechanisms, attributing functional and structural roles for analogous conserved structural motifs lying adjacent to the catalytic transfer centre [1,12].…”
Section: Introductionmentioning
confidence: 99%